Four Quadrant Osteoplastic Decompressive Craniotomy versus Conventional Decompressive Craniectomy for Traumatic Brain Injury: A Randomized Controlled Trial - Vankipuram, Siddharth; Sasane, Sumeet V.; Chandra, Anil; Ojha, Bal Krishna; Singh, Sunil K.; Srivastava, Chittij; Jaiswal, Somil; Bajaj, Ankur (Indian Journal of Neurotrauma, 2017)
Objective Four quadrant osteoplastic decompressive craniotomy (FoQOsD) has been described as a novel technique in the management of patients with traumatic brain injury requiring decompressive surgery. There has not been a randomized controlled trial comparing its outcomes with conventional decompressive craniectomy (DECRA) as yet.Methods A randomized controlled trial of 55 patients was conducted, of whom 29 underwent DECRA and 26 patients underwent FoQOsD. The preoperative baseline demographics, clinical conditions, and radiologic features were similar in both the groups. Clinical outcome was decided by the use of Glasgow coma outcome scale extended (GOS-e) at 3 months. Radiographic outcomes were assessed by measurement of the change in midline shift and brain width expansion (ipsilateral and contra-lateral to hematoma) on the postoperative computed tomographic (CT) scan.Results No significant differences were identified in baseline demographics, clinical condition, Rotterdam CT score, and radiographic characteristics between both the groups. At 3-month follow-up, the mean GOS-e score was comparable in both the groups (3.23 in DECRA group and 3.35 in FoQOsD group, p = 0.856). Mortality analysis at 3 months revealed that nine patients died in the DECRA group and eight died in FoQOsD group. Postoperative imaging characteristics, including Rotterdam score, also did not differ significantly. The percentage reduction in midline shift and percentage brain width expansion on the postoperative CT scan was similar in both the groups (p > 0.05).Conclusion FoQOsD appears to be at least as efficacious as DECRA in providing equivalent clinical outcomes with the added benefit of avoiding a second surgery.
Keywords: four quadrant osteo-plastic decompressive craniotomy; conventional decompressive craniectomy; novel decompression technique; syndrome of trephined; traumatic brain injury; randomized controlled trial